Transformation of Muslim Family Education in the Digital Era: From Traditional to Modern - Izi, Arilana Nur; Salim, Hakimuddin (Universitas Muhammadiyah Surakarta, 2023)
Education in the context of the Muslim family, focuses on the principles of Islamic religious sharia. tsawabit, which is something that remains in the religion of Islam that must not change at any time, but at the same time there is a mutaghayyirat nature that is flexible and dynamic. In the education of Muslim families in the Digital Era, it is important that there is dynamism with the times but still in accordance with the principles of Islamic religious law. Modernization is not something substantial to oppose if it is still in accordance with the tenets of Islamic teachings. The family is the smallest element of society that has a great role in the formation of the nation. Parents have an important role in family education and become the initial foundation for character and religious education. Parents in the modern era partly consider the education obtained by children in school to be sufficient so that they pay less attention to education, especially religious education in the family environment. This paper aims to explain and identify the forms of transformation of Muslim family education in the Digital Era, from traditional to modern that utilize digital technology.